DEVELOPMENT OF INTELLECTUAL CHAT-BOT OF THE OFFICE OF INTERNATIONAL COOPERATION - Paziak , А.C.; Diahyleva , О.С.; Leschenko , А.М.; Yurzhenko , А.Ю. (Journal of Information Technologies in Education (ITE), 2020)
The article describes the development and use of an intelligent chat bot as a means of visualizing content and to gain access to information systems of the Office of International Cooperation. It is emphasized that a characteristic feature of modernity is the formation and rapid development of the information society with a clear transition to innovative models of development in all spheres of society. Chat bot is described as popular and universal tool for communication and digital competence formation, its advantages are pointed out. Scientific works of foreign and domestic researchers on this issue are analyzed, in which the approaches to the creation of chatbots, features of structure and design are highlighted, the state and reasons for the demand for this means of communication are characterized. The procedure of creating the intelligent chat bot of the Office of International Cooperation to simplify the communication system between the department and students, employees in the information technology environment is described. Qualification of chatbots is provided. It is noted that Telegram, unlike other messengers, as a platform, allows the chat bot to perform various operations with both messages and chats. BotFather was used to develop the bot. The article describes commands for editing the bot, which allow you to change its name, description, public information about the bot, profile image, list of commands that the bot supports, or configure and delete the bot. Various bot commands have been created, the work on which is explained step by step and in detail and illustrated. The bot added links to social networks of the Office of International Cooperation of the Kherson State Maritime Academy. It is emphasized that the use of intelligent chat bots has apotential educational, informational opportunity as an alternative tool for the formation of pedagogical competence of employees of academy and applicants for higher education in the educational and methodological work of department. We see prospects for further research in studying the use of other opportunities to expand the functionality of the intelligent chat bot of the Office of International Cooperation of the Kherson State Maritime Academy.